Optimisation model for maximizing economic impact of POME treatment system - Che Man, Hasfalina; Pallikodathan, Sivakumar; Mohamad Shukery, Mohamad Firdza; Mohd Ghazi, Tinia Idaty; Sulaiman, Alawi; Nagarajoo, Gunasilan (Penerbit UniMAP, 2024)
This study presents a strategic planning model to optimize economic returns and minimize the environmental impact of Palm Oil Mill Effluent (POME) treatment systems. The model aims to maximize profits while reducing CO2e emissions by evaluating three treatment options: Anaerobic Digester Tank System (ADT), Covered Lagoon (CL) with biogas capture, and Open Pond System (OP). Constraints considered include fresh fruit bunch (FFB) production, POME generation, treatment system capacity, electricity generation from the existing boiler and additional biogas engine, electricity demand, capital costs, and operating costs. A mixed-integer linear programming model (MILP) is formulated and optimized using GAMS 40.1.0 software, focusing on selecting the treatment system that balances profitability with minimal CO2e emissions. Applied to a case study of two mills in Papua New Guinea, the model identified the ADT system as the optimal treatment system. In the Economic Mode, the model prioritizes profit maximization, achieving a total annual profit of USD 9,769,439, with electricity sales amounting to USD 12,399,439 per year. The developed model can assist governmental agencies and private sectors in developing strategic pome treatment systems that enhance profitability while minimizing environmental impact.